Early evaluation and on field conditions of resistance to Mycosphaerella fijiensis Morelet of plants from Grande naine (AAA) cultivar, obtained through out tissue culture and mutations induction - Lourdes R. García; Juan Pérez Ponce; Pedro Orellana; Idalmis Bermúdez-Caraballoso; Novisel Veitía; Michel Leiva-Mora; Yelenys Alvarado-Capó; Carlos Romero; Mayra Acosta-Suárez (Biotecnología Vegetal, 2003)
The present work was carried out in the Plants Biotechnology Institute of the Central University of Las Villas. The plant material from the cv. Grande Naine (AAA) was treated with physical mutagenic agents(gamma radiation 60Co source) to induce genetic variability. The behaviour of the population to the black Sigatoka was evaluated. A somaclone was selected by its disease resistance and was in vitro multiplied and the plants were acclimatized to evaluate its behaviour facing the disease on greenhouse conditions and in a second cycle of multiplication in the field. The results showed that in the majority of the plants were not found differences respect cv Grande Naine, just one presented similar reaction to cv. ‘FHIA 18’ (AAAB) (partially resistant) as for the variable evaluated, being obtained a frequency of 0.018% for this character. This plant was named IBP 446. After 60 days of application of the mycelial homogenized of M. fijiensis in micropropagated plants of this somaclone, differences in the respect affectation states were found at susceptible witness in greenhouse conditions. When plants of the IBP 446 were evaluated in a second cycle of multiplication differences were found with the susceptible control only at flowering, while they behaved similar at susceptible control in the crop.